Anesthesia and Perioperative Care for Organ Transplantation - Subramaniam, Kathirvel; Sakai, Tetsuro (Springer New York : Imprint: Springer, 2017)
This comprehensive textbook, covering all aspects of the perioperative management of patients undergoing organ transplantation, serves as the standard reference for clinicians who care for transplant patients on a day-to-day basis as well as those who encounter organ transplantation only occasionally in their clinical practice. Anesthesia and Perioperative Care for Organ Transplantation covers transplantation of the heart, lung, liver, pancreas, and kidney, as well as multivisceral and composite tissue graft transplantations. For each kind of transplantation, the full spectrum of perioperative considerations is addressed: preoperative preparation, intraoperative anesthesia management, surgical techniques, and postoperative care. Each chapter contains evidence-based recommendations, relevant society guidelines, management algorithms, and institutional protocols as tables, flow diagrams, and figures. Photographs demonstrating surgical techniques, anesthesia procedures, and perfusion management are included. Anesthesia and Perioperative Care for Organ Transplantation is for anesthesiologists and critical care physicians; transplantation surgeons; nurse anesthetists; ICU nurses; and trainees.- Resumé vydavatel
Keywords: anesteziologie; transplantace; perioperační péče; anesthesiology; transplantation; perioperative care; elektronické knihy; sborníky; electronic books; papers of several authors